INTELLECTUAL PROPERTY ISSUES IN INTERNATIONAL PRIVATE LEGAL RELATIONS (World Bulletin of Management and Law, 2023)
This article explores the intricate landscape of intellectual property (IP) issues in international private legal relations. In an era of globalized commerce, the protection and enforcement of intellectual property rights across borders have become paramount. The study delves into the challenges posed by the diverse legal systems, jurisdictional complexities, and conflicting laws that often arise in cross-border disputes. Through a comprehensive literature analysis, the article examines existing legal frameworks, enforcement mechanisms, and the impact of international agreements, such as the TRIPS Agreement. The methods section outlines the approaches taken by nations to address these issues. The results section presents an overview of the current state of international IP protection, and the discussion section critically analyzes the strengths and weaknesses of existing mechanisms. The article concludes with suggestions for improving the legal landscape and fostering greater international cooperation in safeguarding intellectual property rights.